2006
DOI: 10.1111/j.1600-6143.2006.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Flow Reserve by Contrast-Enhanced Echocardiography: A New Noninvasive Diagnostic Tool for Cardiac Allograft Vasculopathy

Abstract: Noninvasive tests have proven unsatisfactory in cardiac allograft vasculopathy (CAV) diagnosis. We assessed coronary flow reserve (CFR) by contrastenhanced transthoracic echocardiography (CE-TTE) in heart transplantation (HT). CFR was assessed in the left anterior descending coronary artery in 73 HT recipients (59 male, aged 50 ± 12 years at HT), at 8 ± 4.5 years post-HT. CFR measurements were taken blindly from coronary angiographies. CFR cut points were the standard value of ≤2 and those defined by receiver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…14 Conversely, the new noninvasive technique for assessing CFR, applied here, provides a relatively simple, readily available, objective, rapid, and repeatable noninvasive diagnostic tool for CAV detection. 9 Thus, our data provide a rationale for including coronary flow velocity pattern and CFR by CE-TTE as noninvasive tools in future clinical trials aimed at assessing new immunosuppressive and antiatherosclerotic agents for CAV prevention or stabilization. 15 In keeping with our study, Hollenberg et al, using invasive Doppler flow wire, reported the relationship between abnormal microvascular response and the clinical end points of angiographically significant CAV, ischemic events, and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Conversely, the new noninvasive technique for assessing CFR, applied here, provides a relatively simple, readily available, objective, rapid, and repeatable noninvasive diagnostic tool for CAV detection. 9 Thus, our data provide a rationale for including coronary flow velocity pattern and CFR by CE-TTE as noninvasive tools in future clinical trials aimed at assessing new immunosuppressive and antiatherosclerotic agents for CAV prevention or stabilization. 15 In keeping with our study, Hollenberg et al, using invasive Doppler flow wire, reported the relationship between abnormal microvascular response and the clinical end points of angiographically significant CAV, ischemic events, and death.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently applied a new noninvasive technique based on contrastenhanced transthoracic echocardiography (CE-TTE) for assessing CFR in the left anterior coronary descending artery (LAD) in HT patients. 8,9 CFR by CE-TTE has been shown to correlate with angiographically detectable coronary artery lesion severity as well as intracoronary Doppler flow wire measurements. 10 However, there is no clear noninvasive marker of outcome in HT.…”
mentioning
confidence: 99%
“…The increase of CFR after tadalafil in our patients cannot be attributed to hemodynamic variations, since heart rate and mean aortic pressure were not significantly different before or after tadalafil, either in basal condition or after adenosine infusion (Table 1); moreover, in previous studies we demonstrated the capacity of non-invasive CFR detected by Doppler echocardiography to be a reliable marker of coronary microvascular impairment in CAD and other cardiac diseases. [19][20][21] This suggests that tadalafil can induce significant coronary microcirculatory vasodilatation, by the observation of nonsignificant changes in basal coronary flow velocity in the absence of flow limiting stenosis of the epicardial vessels. Our study did not attempt to assess the side effects of the drug, but to reveal a potentially long-acting, beneficial effect on coronary microcirculation in patients with known CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Tona et al [45] demonstrated feasibility and prognostic value of coronary flow reserve measured by contrast enhanced echocardiography with good correlation with major acute cardiac events. Severe Coronary Flow Reserve (CFR) alteration was shown to precede acute cardiac event impact on prognosis [27] and this probably relates to the limited number of studies, each with differing analysis methodology.…”
Section: Ivusmentioning
confidence: 99%